Embedding and Interpolation for Some Paralogics. The Propositional Case - Batens, Diderik; De Clercq, Kristof; Kurtonina, Natasha (Reports on Mathematical Logic, 1999)
We consider the very weak paracomplete and paraconsistent logics that are obtained by a straightforward weakening of Classical Logic, as well as some of their maximal extensions that are a fragment of Classical Logic. We prove (for the propositional case) that these logics may be faithfully embedded in Classical Logic (as well as in each other), and that the interpolation theorem obtains for them.